Kepuasan Kerja, Komitmen Organisasi dan Turnover Intention : Studi pada Pegawai Honorer di Kabupaten Grobogan - Setyaningrum, Nurma Adi; Cahyono, Edi (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2021)
Abstract— The purpose of this study is to examine the effect of job satisfaction and organizational commitment on turnover intention. Data were collected from 60 honorary employees at regency Grobogan by using a convenience sampling. The statistical method is multiple regression analysis. The result of this research which is showed that job satisfaction and organizational commitment have a positive and significant effect on turnover intention. Keywords—: Job Satisfaction; Organizational Commitment; Turnover Intention.